2011
DOI: 10.1002/jcb.23360
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell volume by glycosaminoglycans

Abstract: Cell volume is regulated by a delicate balance between ion distribution across the plasma membrane and the osmotic properties of intra- and extracellular components. Using a fluorescent calcein indicator, we analysed the effects of glycosaminoglycans on the cell volume of hyaluronan producing fibroblasts and hyaluronan deficient HEK cells over a time period of 30 h. Exogenous glycosaminoglycans induced cell blebbing after 2 min and swelling of fibroblasts to about 110% of untreated cell volume at low concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Hyaluronidase digestion or inhibition of hyaluronan export led to intracellular alkalization indicating the phenomena were physiological. As discussed previously (Joerges et al, ), the concentration range of glycosaminoglycans up to 2 mg/ml were also physiological. Adjustment was extremely fast, because the final intracellular pH had been already reached after 5 sec, the earliest measurable time point.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Hyaluronidase digestion or inhibition of hyaluronan export led to intracellular alkalization indicating the phenomena were physiological. As discussed previously (Joerges et al, ), the concentration range of glycosaminoglycans up to 2 mg/ml were also physiological. Adjustment was extremely fast, because the final intracellular pH had been already reached after 5 sec, the earliest measurable time point.…”
Section: Discussionsupporting
confidence: 64%
“…Donnan effects of extracellular glycosaminoglycans were also responsible for membrane depolarization (Hagenfeld et al, 2010) which were attributed to K þ influx or to cell swelling and blebbing which were mediated by volume sensitive chloride influx (Joerges et al, 2012). Similarly, extracellular hyaluronan caused Ca 2þ influx through postsynaptic Ca 2þ channels (Kochlamazashvili et al, 2010).…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, local glycosaminoglycans concentration led to Donnan effects that exceed their concentration in solution causing depolarisation of the membrane potential [Hagenfeld et al, ], cell swelling [Joerges et al, ] and intracellular acidification [Kathagen and Prehm, ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that extracellular glycosaminoglycans have profound effects on fundamental cellular properties. They reduce the membrane potential [Hagenfeld et al, ], alter the cell volume [Joerges et al, ] and decrease the intracellular pH [Kathagen and Prehm, ]. These phenomena were independent of the CD44 receptor and can be explained by Donnan effects.…”
mentioning
confidence: 99%